HARMONIZING ECONOMIC GROWTH AND ENVIRONMENTAL PRESERVATION: DECOUPLING POLLUTION FROM PROSPERITY - Huang 1, Zihang (PEOPLE: International Journal of Social Sciences, 2024)
Environmental pollution and climate change effects being experienced by present global populations can be attributed to economic growth. With the increase in industrialization, the generation of waste without proper treatment and disposal has resulted in polluted air that risks the health of the population. It has also resulted in increased global earth temperatures, which have in turn affected the agricultural productivity of the earth, a primary source of livelihood for human populations. Despite these great consequences, there can be a harmonious existence of economic growth and reduced environmental pollution through decoupling. Government efforts are critical in the implementation of decoupling efforts, with their commitments expressed through policies and legislation.